Presidential Decree-Law No. 82 of the Year 2013 On Amending Certain Provisions of the Issuing Articles of Law No. 89 of the Year 1998 On Organizing Tenders and Bids And Some Provisions of the Said Law = قرار رئيس جمهورية مصر العربية بالقانون رقم 82 لسنة 2013 فى شأن تعديل بعض أحكام القانون رقم 89 لسنة 1998 بإصدار قانون تنظيم المناقصات والمزايدات وبعض أحكام قانون تنظيم المناقصات والمزايدات - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.